Association of Psychological Characteristics and Functional Dyspepsia Treatment Outcome: A Case-Control Study - Yiping Chen; Caihua Wang; Jinyu Wang; Leilei Zheng; Weibo Liu; Huichun Li; Shaohua Yu; Bin Pan; Hualiang Yu; Risheng Yu (Gastroenterology Research and Practice)
This study was to investigate the association of psychological characteristics and functional dyspepsia treatment outcome. 109 patients who met the criteria for FD were enrolled. Eysenck Personality Questionnaire (EPQ), Symptom Checklist 90 (SCL90), and the Pittsburgh Sleep Quality Index (PSQI) were used to measure personality, psychological symptoms, and sleep quality in our patients. Leeds Dyspepsia Questionnaire (LDQ) was used to assess dyspeptic symptoms at baseline and after eight weeks of treatment. The LDQ scores change after therapy, and the degraded rate of LDQ was used to assess the prognosis of patients. Logistic regression model was used to assess the effect of the personality, psychological symptoms, and sleep quality on the prognosis of patients. Our result revealed that poor sleep quality (OR=7.68, 95% CI 1.83–32.25) and bad marriage status (OR=1.22, 95% CI 1.10–1.36) had the negative effect on the prognosis of FD, while extroversion in personality traits (OR=0.86, 95% CI 0.76–0.96) had positive effect on the prognosis of FD. We should pay attention to the sleep quality, the personality, and the marriage status of FD patients; psychological intervention may have benefit in refractory FD.